The Microbiome How our Inner Ecosystem Controls the Immune System and Prevents Inflammation - Lucius, Richard (Springer, 2025)
This book unravels in an easily understandable way the exciting molecular connections between our gut microbiome, i.e. the collective microorganisms that we carry in our digestive system, nutrition and the immune system, and how an imbalance can lead to the development of inflammatory diseases. The totality of these gut microorganisms forms a complex ecosystem within us, consisting of hundreds of different species of bacteria.The author, microbiologist Professor Richard Lucius, introduces the historical context of microbiome research, discusses how our lives have changed in recent decades, and explains the composition and function of the microbiome and its connection to the gut and immune system. The book explains in detail and supported with appealing illustrations how allergies, chronic intestinal inflammation, type 1 diabetes, multiple sclerosis, rheumatoid arthritis, psoriasis and coeliac disease develop.
Keywords: Mikroflora; Hardcover, Softcover / Biologie/Mikrobiologie; Mikrobiologie; Nichtklinische Fächer